2020
DOI: 10.1371/journal.pone.0238422
|View full text |Cite
|
Sign up to set email alerts
|

SSNdesign—An R package for pseudo-Bayesian optimal and adaptive sampling designs on stream networks

Abstract: Streams and rivers are biodiverse and provide valuable ecosystem services. Maintaining these ecosystems is an important task, so organisations often monitor the status and trends in stream condition and biodiversity using field sampling and, more recently, autonomous in-situ sensors. However, data collection is often costly, so effective and efficient survey designs are crucial to maximise information while minimising costs. Geostatistics and optimal and adaptive design theory can be used to optimise the place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This is not overly surprising because of the nature of eDNA transport in rivers, but also, our data set contained many site pairs in close proximity (1 km) to identify the upstream-edge boundaries in tributaries. Furthermore, quantification of spatial autocorrelation in our eDNA data set adds valuable information to the body of literature focused on optimally designing sampling on river networks (Som et al 2014;Pearse et al 2020;Carraro et al 2021). Our sites were most correlated at hydrological distances ≤10 km, implying sampling at finer intervals for species distribution modeling may be redundant.…”
Section: Modelmentioning
confidence: 99%
“…This is not overly surprising because of the nature of eDNA transport in rivers, but also, our data set contained many site pairs in close proximity (1 km) to identify the upstream-edge boundaries in tributaries. Furthermore, quantification of spatial autocorrelation in our eDNA data set adds valuable information to the body of literature focused on optimally designing sampling on river networks (Som et al 2014;Pearse et al 2020;Carraro et al 2021). Our sites were most correlated at hydrological distances ≤10 km, implying sampling at finer intervals for species distribution modeling may be redundant.…”
Section: Modelmentioning
confidence: 99%
“…Furthermore, the optimal placement of sensors will optimize simulations, improving performance in the light of low computational costs [233]. In streamflows, the efficiency of distributed computing has been used to enhance the monitoring system by optimizing adaptive design [234]. However, some obstacles of water bodies change over time and their remote location has determined the monitoring efficiency of the network from different sensor locations [235].…”
Section: E Sensor Placement and Sampling Point Identificationmentioning
confidence: 99%
“…Adaptive design has also been used in video surveillance applications to adjust the sampling rates of cameras based on the present circumstances (Jain & Chang, 2004; Jiao et al, 2004), and in habitat monitoring to change sampling frequencies depending on observed behavior (Mainwaring et al, 2002). Only a few studies have used adaptive designs in other fields (Morgan et al, 2014), and, in particular, adaptive design has received little attention in ecological and environmental monitoring (Falk et al, 2014; Pearse et al, 2020). Despite the fact that adaptive ecological monitoring has seen some interest, the approaches that have been proposed tend to rely on changes in survey designs as new problems occur (Lindenmayer et al, 2011) rather than using adaptive design to update the survey design based on feedback between models and the data being collected, to efficiently estimate specific quantities of interest.…”
Section: Introductionmentioning
confidence: 99%